A NEW SPECIES OF AGALMYLA (GESNERIACEAE) FROM SULAWESI - Middleton, D. J.; Scott, S. M. (Edinburgh Journal of Botany, 2008)
A new species of Gesneriaceae from Sulawesi, Agalmyla hilliardiae D.J.Middleton & S.Scott in Agalmyla sect. Exannularia, is described and illustrated.
Keywords: Agalmyla; Gesneriaceae; new species; Sulawesi